Reinforcement of hydroxyethyl cellulose / poly (vinyl alcohol)with cellulose nanocrystal as a bone tissue engineering scaffold - Farah Hanani, Zulkifli; Nor Sarahtul Nadirah, Hairol Nizan (Springer Netherlands, 2020)
n this present work, a porous three-dimensional (3D) scaffoldof HEC/PVA and HEC/PVA/CNC were successfully fabricated byfreeze-drying technique. HEC (5 wt%) and PVA (15 wt%) were dissolved and blended at a ratio of 50:50 and incorporated withCNC (3 wt%) as nanofillers to obtain a highly porous scaffolds. Themorphology, chemical and thermal properties of scaffolds werecharacterized by SEM, ATR-FTIR, and TGA. Meanwhile, cytotoxicity studies on both porous scaffold biomaterials were carriedout by utilizing human fetal osteoblast (hFOB) cells using MTT assays. Incorporated HEC/PVA with CNC were exhibited superiorfunctionality which resulted in decreasing average pore size from ~54.1μmto~33.4μm. There were slightly changes in thechemical structure as determined by FTIR spectra. Thermal studies revealed that the melting temperatures of HEC/PVA/CNCscaffold were slightlyshifted to a higher value. It was observed that hFOB cells were able to attach and spread on both scaffolds andsupported the cell adhesion and proliferation. Due to its biocompatible and biodegradable properties, these newly developed highlyporous scaffolds may provide a promising alternative scaffolding matrix for bone tissue engineering regeneration.